Cloning and characterization of two rhamnogalacturonan hydrolase genes from Aspergillus niger. - Suykerbuyk, M E (1997)
A rhamnogalacturonan hydrolase gene of Aspergillus aculeatus was used as a probe for the cloning of two rhamnogalacturonan hydrolase genes of Aspergillus niger. The corresponding proteins, rhamnogalacturonan hydrolases A and B, are 78 and 72% identical, respectively, with the A. aculeatus enzyme. In A. niger cultures which were shifted from growth on sucrose to growth on apple pectin as a carbon source, the expression of the rhamnogalacturonan hydrolase A gene (rhgA) was transiently induced after 3 h of growth on apple pectin. The rhamnogalacturonan hydrolase B gene was not induced by apple pectin, but the rhgB gene was derepressed after 18 h of growth on either apple pectin or sucrose. Gene fusions of the A. niger rhgA and rhgB coding regions with the strong and inducible Aspergillus awamori exlA promoter were used to obtain high-producing A. awamori transformants which were then used for the purification of the two A. niger rhamnogalacturonan hydrolases. High-performance anion-exchange chromatography of oligomeric degradation products showed that optimal degradation of an isolated highly branched pectin fraction by A. niger rhamnogalacturonan hydrolases A and B occurred at pH 3.6 and 4.1, respectively. The specific activities of rhamnogalacturonan hydrolases A and B were then 0.9 and 0.4 U/mg, respectively, which is significantly lower than the specific activity of A. aculeatus rhamnogalacturonan hydrolase (2.5 U/mg at an optimal pH of 4.5). Compared to the A enzymes, the A. niger B enzyme appears to have a different substrate specificity, since additional oligomers are formed.